2020
DOI: 10.3390/plants9091149
|View full text |Cite
|
Sign up to set email alerts
|

Response of Downy Oak (Quercus pubescens Willd.) to Climate Change: Transcriptome Assembly, Differential Gene Analysis and Targeted Metabolomics

Abstract: Global change scenarios in the Mediterranean basin predict a precipitation reduction within the coming hundred years. Therefore, increased drought will affect forests both in terms of adaptive ecology and ecosystemic services. However, how vegetation might adapt to drought is poorly understood. In this report, four years of climate change was simulated by excluding 35% of precipitation above a downy oak forest. RNASeq data allowed us to assemble a genome-guided transcriptome. This led to the identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Additionally, about 71% and 57% of the unitranscripts and predicted proteins were successfully assigned to genes by BLASTx and BLASTp searches against the UniProtKB/Swiss-Prot database (Table S9) which is similar to previous mangrove study and higher than that of another tree species; Downy Oak (Quercus pubescens Willd.) [38].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, about 71% and 57% of the unitranscripts and predicted proteins were successfully assigned to genes by BLASTx and BLASTp searches against the UniProtKB/Swiss-Prot database (Table S9) which is similar to previous mangrove study and higher than that of another tree species; Downy Oak (Quercus pubescens Willd.) [38].…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptome assembly contained more than 90% of genes represented at the available orthologue groups ( Table 1 ). Furthermore, about 60% of the unitranscripts and 57.5% of the predicted proteins were assigned to genes, by searches through BLASTx and BLASTp against the UniProtKB/Swiss-Prot database ( Table S10 ) which is similar to the previous mangrove study [ 8 ] and higher than that of other tree species such as Downy Oak ( Quercus pubescens ) [ 29 ].…”
Section: Discussionmentioning
confidence: 69%
“…The priority in current research into Quercus spp. is the response to stresses and climate change conditions, and this has been approached using a comparative transcriptomic approach in different species [ 90 , 91 , 92 , 93 ]. A comparison of the least drought-tolerant deciduous Q. robur , quite tolerant deciduous Q. pubescens , and the most tolerant evergreen Q. ilex revealed common and species-specific responses [ 94 ].…”
Section: The “Omics” and Their Integration With Other Approaches (How)mentioning
confidence: 99%
“…A few studies have dealt with responses to drought and climate change conditions. In a four-year Q. pubescens drought trial, GC-MS metabolomics revealed that tolerance implicates the tricarboxylic acid cycle shunt through the glyoxylate pathway, and the galactose metabolism by reducing carbohydrate storage and increasing proteolytic activity [ 92 ]. Changes in the phenolic pattern in Q. suber during drought and recovery treatments have been reported [ 144 ], and the process of metabolite resorption from plant leaves during senescence has been evaluated under drought and warming conditions in Q. rubra [ 145 ].…”
Section: The “Omics” and Their Integration With Other Approaches (How)mentioning
confidence: 99%